Study of Ms Media With Addition Of Auxins And Cytokinin on Growth and Development of Arr (Arenga Pinnata (Wurmb) Merr.) Culture. - Muhammad, Alqamari; Bismar , Thalib; FS, Harahap (Jurnal Online Pertanian Tropik, 2020)
Aren has an important role as a biofuel producer, so research is needed for the development of this plant. This research has been carried out in the Tissue Culture Laboratory of the Department of Agrotechnology, Faculty of Agriculture, Muhammadiyah University, North Sumatra, from October 2017 to September 2018. This study aims to obtain a combination of concentrations of growth regulators of curcumin and cytokines which are best for increasing plant population in vitro culture. , as well as to produce large quantities of quality plantlets in a relatively short time. Experiments in the form of a Completely Randomized Design (CRD) were repeated 3 times with 5 samples of each treatment to obtain 105 units of experimentation. The first series experiment was the regeneration stage, shoot tip results were cultured on WPM media with a concentration of 0.25 ppm + 1.0 ppm Kinetin which was used as explants. Furthermore, the shoots were regenerated in the WPM medium with the treatment of concentration of growth regulators of auxin and cytokinin which consisted of 7 treatment levels, namely (E0) 0.00 ppm NAA + 0.00 ppm BAP, (El) 0.00 ppm NAA + 0.25 ppm BAP, (E2) 0.50 ppm NAA + 0.00 ppm BAP, (E3) 0.50 ppm NAA + 0.50 ppm BAP, (E4) 0.00 ppm NAA + 0.75 ppm BAP, (E5) 0.50 ppm NAA + 0.75 ppm BAP, (E6) 1.00 ppm NAA + 1.00 ppm BAP. From the observed variables, the percentage of live explants and percentage of explants forming callus the best results were found in a combination of 1.00 ppm NAA + 1.00 ppm BAP (E6) concentration.   References Asikin D, Puspitaningtyas DM. 2000. Studi perkecambahan biji aren (Arenga pinnata (Wurm) Merr.) secara in vitro dan in vivo. Di dalam: Prosiding Seminar Hasil Penelitian dan Pengembangan Bioteknologi III. 2000 Maret 7- 9; Cibinong, Indonesia. Cibinong (ID). hlm 411-419. Doods AH, Roberts LW. 1999. Experiments in Plant Tissue Culture 3rd Ed. Cambridge (GB). Cambridge University Press. Harahap, P., Harahap, E.M., Harahap, D.E. and Harahap, F.S., 2018. Eksplorasi dan Identifikasi Tanaman Aren (Arenga pinnata Merr) di Kabupaten Tapanuli Selatan. Jurnal Pertanian Tropik (Indonesian Tropical Agriculture Journal) accredited by KEMENRISTEK DIKTI No: 21/E/KPT/2018, 5(3, Dec), pp.423-427. Harahap, P., Harahap, M.K. and Harahap, F.S., 2019. Identifikasi Karakter Fenotip Daun Tanaman Aren (Arenga pinnata Merr) di Kabupaten Tapanuli Selatan. Jurnal Pertanian Tropik (Tropical Agriculture Journal) accredited by KEMENRISTEK DIKTI No: 21/E/KPT/2018, 6(3, Dec), pp.472-476. George EF, Sherrington PD. 1984. Plant Propagation by Tissue Culture: Handbook and Directory of Commercial Laboratories. England (GB): Exegetic Ltd. Gomez, K.A. and Gomez, A.A., 1995. Prosedur statistik untuk penelitian pertanian. Edisi ke, 2. Gunawan LW. 1987. Teknik Kultur Jaringan. Bogor (ID): Pusat Antar Universitas (PAU) IPB. Julianti, Reine Suci Wulandari, dan Herlina Darwati. 2013. Penambahan NAA dan BAP Terhadap Multiplikasi Subkultur Tunas Gaharu (Aquilaria Malaccensis Lamk). Jurrnal Hutan Lestari. Karjadi,AK dan A.Buchori. 2007. Perkecambahan dan Perbanyakan Gaharu secara In Vitro. Jurnal Hort. Rofik A, Murniati E. 2008. Pengaruh perlakuan deoperkulasi benih dan media perkecambahan untuk meningkatkan viabilitas benih aren (Arenga pinnata (Wurmb) Merr.). Bul Agron. 36: 33-40. Rozen, Nalwida. 1989. Pengaruh suhu awal perendaman terhadap pemecahan dormansi enau (Arenga pinna/a (Wumrb) Merr) dan pertumbuhan bibit dipersemaian. Tesis. Fakultas Pertanian Universitas Andalas Padang. Rusmin, Devi. 1992. Pengaruh lama pemberian periode gelap terhadap perkecambahan benih enau (Arenga pinnata (Wumrb) Men) dan pertumbuhan bibit di persemaian Tesis. Fakultas Pertanian Universitas Andalas. Padang. Masyudi, M.F. 1992. Pengaruh zat pengatur tumbuh 2,4- D dan BAP pada kultur jaringan biji padi rnasak panen, dalam; Bulettin Pertanian. Jakarta. 12 (1). P: 1 -7. Moore, T.C. 1979. Biochemistry and Physiology of plant hormones. Springer-Verlag, New York. 174 p. Murashige T, Huang LC. 1985. Organogenesis in vitro: structural, physiological, and biochemical aspects.in  Biotechnology in International Agricultural Research. International Agricultural Research Center (IARCs) and Biotechnology; 1984 April 23-27; Manila (PH): IRRI. p.227-240. Nisak, K., Tutik Nurhidayati, dan Kristanti I.Purwani. (2012). Pengaruh Kombinasi konsentrasi ZPT NAA dan BAP pada Kultur Jaringan Tembakau Nicotiana tabacum var. Prancak 95. Jurnal Sains Dan Seni Pomits Saleh MS, Wardah. 2010. Perkecambahan benih aren dalam kondisi terang dan gelap pada berbagai konsentrasi GA3. J. Agrivigor. 10:18-25. Satria, B. 1995. Perbanyakkan manggis (Garcinia mangostana L.) dengan menggunakan eksplan hipokotil .pada kombinasi dosis arang aktif dengan komposisi konsentrasi BAP dan NAA secara in vitro. Universitas Andalas Padang. 105 hal. Sirait D. 2010. Pengaruh skarifikasi bagian-bagian benih dan konsentrasi asam giberelat (GA3) terhadap perkecambahan benih aren (Arenga pinnata L.) [Skripsi]. Medan (ID): Universitas Sumatera Utara. Usman MA. 2006. Pengaruh tingkat kemasakan dan pematahan dormansi benih aren (Arenga pinnata (Wurmb.) Merr.) pada kondisi media yang berbeda [Skripsi]. Bogor (ID): Instititut Pertanian Bogor’ Wattimena GA. 1988. Zat Pengatur Tumbuh Tanaman. Bogor (ID): Pusat Antar Universitas (PAU) IPB. Wattimena GA, Gunawan LW, Mattjik NA, Syamsudin E, Wiendi NMA, Ernawati A. 1992. Bogor (ID): Pusat Antar Universitas (PAU) IPB. Widyawati N, Tohari, Yudono P, Soemardi I. 2009. Permeabilitas dan perkecambahan benih aren (Arenga pinnata (Wurmb.) Merr). J. Agron. Indonesia. 37:152-158.